2008
DOI: 10.1002/ajmg.b.30808
|View full text |Cite
|
Sign up to set email alerts
|

5‐HTTLPR genotype and anxiety‐related personality traits: A meta‐analysis and new data

Abstract: We investigated the strength of evidence for association of the 5-HTTLPR polymorphism and the personality trait of Harm Avoidance. We used new primary data from a large sample of adults drawn from the Finnish population. We also applied meta-analytic techniques to synthesize existing published data. The large number studies of the 5-HTTLPR polymorphism allowed us to apply a formal test of publication bias, as well as formally investigate the impact of potential moderating factors such as measurement instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
157
1
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 92 publications
12
157
1
11
Order By: Relevance
“…Our findings are however consistent with the recent scientific literature, as a large meta-analysis showed that several studies have failed to show association between anxiety-related traits and 5HTTLPR, except neuroticism measured by NEO (Munafo et al, 2009): it has been argued that genetic effects on neuroticism might be complex and smaller than 1% per genetic variants (Shifman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are however consistent with the recent scientific literature, as a large meta-analysis showed that several studies have failed to show association between anxiety-related traits and 5HTTLPR, except neuroticism measured by NEO (Munafo et al, 2009): it has been argued that genetic effects on neuroticism might be complex and smaller than 1% per genetic variants (Shifman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…6 These observations suggest that the short allele of 5HTTLPR has reduced promoter activity, resulting in a decreased gene expression and low serotonin uptake. 15 The short allele has been reported to have a modest role in anxiety-related personality trait 25 and suicidal behavior. 26 Within SLC6A4, STin2 has been reported to be the strongest candidate polymorphism showing susceptibility to schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HA, ' self-directedness ' has often been correlated with serotonergic markers (Allgulander et al 1998 ;Peirson et al 1999 ;Boz et al 2007). Results from these studies should be seen as circumstantial evidence for the hypothesis and inconsistencies remain, as they do in genetic studies on HA and the serotonin system (Lesch et al 1996 ;Schinka et al 2004 ;Sen et al 2004 ;Munafò et al 2009). …”
Section: Introductionmentioning
confidence: 99%